Estudo ergonômico nos discentes da Ufersa – Campus Caraúbas/RN - Silva, José Diego de Aquino (Universidade Federal Rural do Semi-Árido, 2019)
Many researches have shown an increase in health problems occasioned by inadequate postures when sitting in chairs for prolonged periods in a static position, imposing stresses and physiological damage to muscles and ligaments. The postural orientation of adolescents may be directly related to intrinsic and extrinsic phenomena, such as: genetic load, environmental structure and physical conditions in which individuals are inserted. Ergonomics aims to adapt the work to the man, acting in a multidisciplinary way in order to prevent injuries in the students, making the academic environment safer and healthier. Its applicability is quite significant in the academic environment, since students are always making repetitive efforts for prolonged periods in inappropriate environmental conditions or subject to poor postural habits. This research aims to analyze all factors that directly affect the productivity and health of the students of the Federal University of the Semi-Arid, Caraúbas campus. For this, it was used through questionnaires, organizational analysis of the environment and application of the RULA method, in order to judge the level of weakness of the postural habits of the students. Based on the results of the analyzes, it was found that students present postural habits that impair the productivity of their studies, as well as the possibility of developing diseases over time. In general, its application in the university environment allows an organization to be made in the middle, avoiding future problems, improving health and enhancing a better quality of studies.
Monografia
Keywords: Ergonomia; Doenças; Postura; RULA; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA